Heavy-flavour hadron decay leptons in Pb-Pb and Xe-Xe collisions at the LHC with ALICE - Dubla, Andrea (Nuclear physics. A, Nuclear and hadronic physics, 2019)
Heavy quarks, i.e. charm and beauty, are sensitive probes of the medium produced in high-energy heavy-ion collisions. They are produced in the early stage of the collision, mainly in hard partonic scattering processes, and are expected to experience the whole collision evolution interacting with the medium constituents via both elastic and inelastic processes. The nuclear modification factor (RAA) is one of the main experimental observables that allow us to investigate the interaction strength of heavy quarks with the medium. The ALICE collaboration measured the production of open heavy-flavour hadrons via their semi-leptonic decays to electrons at mid-rapidity and to muons at forward rapidity in elementary proton-proton (pp) collisions as well as p-Pb, Pb-Pb and in Xe-Xe collisions.
XXVIIth International Conference on Ultrarelativistic Nucleus-Nucleus Collisions (Quark Matter 2018)
Gesehen am 21.10.2019